Career Paths : Tourism / Virginia Evans, Jenny Dooley, Veronica Garza - Evans, Virginia
The series is organized into three levels of difficulty and offers over 400 vocabulary terms and phrases. Every unit includes a test of reading comprehension, vocabulary, and listening skills, and leads students through real-world examples of written and oral production.